1998
DOI: 10.1093/jnci/90.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cervical Cancer in Thailand: a Case-Control Study

Abstract: New preventive strategies for cervical cancer will require the consideration of multiple HPV types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
128
7
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 15 publications
21
128
7
7
Order By: Relevance
“…Thus, the prevalence of HPV DNA in the male genital tract seems similar to that in the cervix uteri of control women in the same populations and age groups, if not higher (Muñoz et al, 1992;Eluf-Neto et al, 1994;Chichareon et al, 1998;Ngelangel et al, 1998). In agreement with findings in women without cervical neoplasia (Herrero et al, 2000b), HPV 16 and 18 types were relatively rare (i.e., less than one third of penile HPV infections) with the notable exception of Brazilian men, among whom these types accounted for the majority of penile HPV infections.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Thus, the prevalence of HPV DNA in the male genital tract seems similar to that in the cervix uteri of control women in the same populations and age groups, if not higher (Muñoz et al, 1992;Eluf-Neto et al, 1994;Chichareon et al, 1998;Ngelangel et al, 1998). In agreement with findings in women without cervical neoplasia (Herrero et al, 2000b), HPV 16 and 18 types were relatively rare (i.e., less than one third of penile HPV infections) with the notable exception of Brazilian men, among whom these types accounted for the majority of penile HPV infections.…”
Section: Discussionmentioning
confidence: 61%
“…The fieldwork was conducted from 1985 through 1993 in Spain (two studies), Colombia (two studies), Brazil, Thailand, and the Philippines. The detailed methods of each of these studies have been described elsewhere (Muñoz et al, 1992;Bosch et al, 1993;Eluf-Neto et al, 1994;Chichareon et al, 1998;Ngelangel et al, 1998;Castelssague et al, 2002). In brief, case women had newly diagnosed, histologically confirmed ICC or CIS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the time frame, age and education level between the study populations might have contributed to the discrepancy. Although smoking is associated with an increased risk of CC [42], its effect on HPV infection is mixed. Poppe et al [43] found that smoking potentially increased the risk of HPV infection through a local impairment of cell-mediated immunity, although the magnitude of the effect was small.…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence was found at the follicular phase (55%), whereas the cumulative prevalence was 75%. (Schiffman et al, 1993;Chichareon et al, 1998;Ngelangel et al, 1998; Liaw et al, 1999;Walboomers et al, 1999;Andersson et al, 2001;Lehtinen et al, 2001). A systematic review on the role of HPV testing within a cervical cancer screening program showed that the high risk HPV prevalence in CIN 1 ranged from 30 to 65%, in CIN 2 from 40 to 70% and in CIN 3 from 60 to 90% (Cuzick et al, 1999).…”
mentioning
confidence: 99%